The agency of transformational leadership in transmogrifying employee innovative behaviors: a moderated mediation model - Sulafah H. Hariri; Muhammad Zafar Yaqub; Mohammed Awad Alshahrani (Cogent Business & Management)
This study elucidates the moderated-mediated role of transformational leadership (TL) in engendering innovative behaviors among employees (EIBs) while considering perceived self-efficacy (PSE) and perceived stress (PS) as the two mediators and perceived organizational support (POS) as the critical moderating contingency. The underlying theories have been the social exchange theory and the expectancy-value-cost theory. After performing PLS-based structural equation modeling, using SmartPLS 4.0 and PROCESS, on a dataset comprising 419 observations, it was found that TL positively influences EIBs through the two mediators (i.e. PSE and PS). The study also corroborates the moderating role of POS in affecting TL-PSE linkages and the TL-PS association. It has also been found that PSE and PS partially mediate TL-EIB linkage. This partial mediation implies that TL affects employees’ creative behaviors by electrifying PSE and reducing PS. Finally, the moderated mediation effects model indicates that POS moderates the indirect impact of TL on EIBs via the two mediators. Besides furthering the scholarly discourse encompassing the productiveness of TL, the findings offer valuable insights for managers aspiring to foster innovative behaviors among their employees.